HISTOPATHOLOGICAL ANALYSIS OF UTERINE APPENDAGEAL LESIONS: A 2-YEAR STUDY AT TERTIARY HEALTH CENTRE - Sajid, Abdul; NEELIMA ARORA,; DIVYA GOYAL,; KUNAL PUROHIT,; VANITA KUMAR, (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to evaluate the various histopathological patterns of uterine adnexal lesions and their prevalence in different age groups. Methods: This is a prospective study conducted in the Department of Pathology, Sardar Patel Medical College and associated group of hospitals, Bikaner, on specimens of uterine appendageal lesions received from November 1st, 2020 to October 31st, 2022 for histopathological examination. The tissues were processed, then stained sections were examined microscopically and histopathological analysis done. Results: A total of 376 cases were included in the study. Out of these, 212 were ovarian lesions, 149 were tubal lesions, and 4 cases showed involvement of both tube and ovary, whereas 11 showed the lesion of broad ligament. 32% of the lesions were tumorous, of which 73% tumors were benign, 26.2% tumors were malignant, and 0.8% were borderline tumors. Maximum uterine adnexal lesions were encountered in 21–30-year age group. Maximum (55.7%) benign tumors were in 21–40-year age group, whereas maximum (53.1%) malignant tumors were in 41–60-year age group. Mean age was 58.53±12.62 years. Conclusion: Non-neoplastic lesions were more common as compared to neoplastic lesions and benign neoplasms outnumbered the malignant neoplasms. Tubal ectopic pregnancy was the most common non-neoplastic lesion. Ovarian teratoma was the most common benign tumor and serous cystadenocarcinoma was the most common malignant tumor encountered. Malignant tumors affect older age group compared to benign tumors.